2015
DOI: 10.4158/ep14495.cr
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Neuroendocrine Tumors Presenting with Hypercalcitonemia

Abstract: Objective: Pancreatic neuroendocrine tumors (pNETs) can be associated with discrete clinical syndromes due to the secretion of a variety of bioactive substances that are used to confirm the diagnosis and as potential tumor markers. Calcitonin (Ct) is mainly secreted by medullary thyroid carcinoma (MTC) but is also rarely secreted by pNETs, occasionally leading to diagnostic confusion. We report the diagnosis of 4 patients with metastatic pNETs and associated Ct secretion who were initially evaluated for thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…There are some reports in the literature of both operational and non-functioning calcitonin-secreting PanNETs. [7][8][9][10][11][17][18][19][20][21][22][23][24][25][26] The exact incidence of calcitonin expression in these tumours is unknown. Uccela S et al 26 performed a review of the literature and found a predominance of calcitonin-immunoreactive VIPpomas among FPanNETs, contrary to what the authors found in their own study, in which insulinomas predominated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are some reports in the literature of both operational and non-functioning calcitonin-secreting PanNETs. [7][8][9][10][11][17][18][19][20][21][22][23][24][25][26] The exact incidence of calcitonin expression in these tumours is unknown. Uccela S et al 26 performed a review of the literature and found a predominance of calcitonin-immunoreactive VIPpomas among FPanNETs, contrary to what the authors found in their own study, in which insulinomas predominated.…”
Section: Discussionmentioning
confidence: 99%
“…In some of the reported cases of functioning and non-functioning calcitonin-secreting PanNET, calcitonin was requested in the context of nodular thyroid disease. 7,[21][22][23][24][25] In others no thyroid disease was identified, leading to unnecessary total thyroidectomies due to the suspicion of a small MTC. In some case reports, calcitonin-secreting PanNET were diagnosed due to systemic or gastrointestinal symptoms (diarrhoea, abdominal pain, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation